EFFECT OF SIZE OF COMPANY AND LEVERAGE OPERATIONS AGAINST income smoothing MANUFACTURING COMPANY STOCK EXCHANGE IN JAKARTA - Nugroho, Bintoro Wahyu; Nursasmita, Ak., Drs. H. Irfan (Accounting, 2009)
The purpose of this study was to determine whether there is influence of firm size and operating leverage of income smoothing manufacturing companies in Jakarta Stock Exchange. The problem in this research is "(1) Is there a difference between company size grading profit company with no grading company profits, (2) Is there a difference between operating leverage grading company profits with no grading company profits, (3) Are there differences in company size and operating leverage collectively ssama between grading company profits with no grading company earnings in manufacturing companies in Jakarta Stock Exchange. " The method and type of data used in data collection that is kind of secondary data consists of the methods of documentation and literature study method. Technique or method of sampling in this study were manufacturing companies on the JSE has listhing with observation for 3-year period beginning in 2000 to 2002. While the data analysis techniques used include (1) descriptive statistics: company profile, the average standard deviation, maximum, minimum, range, and sum. (2) inferential statistics including univariate test with (Mann Whitney test) and Multivariate testing with (Binary Logistic Regression). Univariate test results show that firm size variable is significant at the number 0000 and operating leverage variables are insignificant in number 0366. So of the two variables that significantly affect the income smoothing is the only variable size companies. While the Multivariate test results showed that the only significant variable of company size with the number 0004 while operating leverage variables are insignificant in number 0390. thus in a multivariate test that significantly influence income smoothing is a variable size of the company. Keyword :firm size, income smoothing.